Impact of oxidative stress SNPs and dietary antioxidant quality score on prostate cancer. (18th May 2020) - Pascual-Geler, M.; Robles-Fernandez, I.; Monteagudo, C.; Lopez-Guarnido, O.; Rodrigo, L.; Gálvez-Ontiveros, Y.; Cozar, J. M.; Rivas, A.; Alvarez-Cubero, M. J.
Abstract: Purpose: To analyse the relation between antioxidant genotypes and Dietary Antioxidant Quality score (DAQs) effect on prostate cancer (PCa) risk and aggressiveness in a Spanish population. Methods: Men ( N  = 155 patients and 152 controls) with PSA values >4 ng/ml were enrolled in the project. DAQs were used considering the daily recommended intake for Spanish people (DRI). Genotyping of 5 SNPs rs662 (PON1), rs10432782 (SOD1), rs4880 (SOD2), rs17650792 (GPX1) and rs1001179 (CAT) were included for the analysis. Results: rs17650792 was statistically significant between case and controls subjects. When comparing D´Amico risk, we found that rs662 (CC), rs10432782 (G allele) and rs17650792 (GG) confer a protection. When testing SNP-antioxidant nutrients interactions, we found an intake of vitamin A and rs100179 (T carriers) and selenium and rs17650792 (G carriers) confers a protection of being in low risk classification. Conclusions: We reported by the first time a correlation between rs662 (PON1) and PCa aggressiveness.